1985
DOI: 10.1037/0022-0167.32.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metaphors and cognitive complexity on perceived counselor characteristics.

Abstract: The effects of three types of counselor-offered metaphors, varying in levels of complexity, were compared to facilitative responses on measures of perceived empathy, regard, expertness, attractiveness, and trustworthiness. Eighty subjects, 32 male and 48 female, crossed on levels of cognitive complexity, were assigned to one of four audiotaped treatment conditions: complex metaphor (CM), narrative analogy (NA), cliche (CL), and Level 3 facilitative response (L3). Results indicated that NA and L3 each produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
1

Year Published

1986
1986
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 11 publications
(13 reference statements)
1
16
1
Order By: Relevance
“…In fact, this study found little support for the idea that exposure to a metaphor can increase divergent thinking in one who hears it. The results of this study were also inconsistent with the findings of Suit and Paradise (1985) in which counselors who used narrative analogy metaphors were rated as more expert.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In fact, this study found little support for the idea that exposure to a metaphor can increase divergent thinking in one who hears it. The results of this study were also inconsistent with the findings of Suit and Paradise (1985) in which counselors who used narrative analogy metaphors were rated as more expert.…”
Section: Discussioncontrasting
confidence: 99%
“…A systematic procedure was used to develop the two treatments. First, characteristics of effective metaphors were drawn from relevant literature (e.g., Ortony, Reynolds, & Arter, 1978;Suit & Paradise, 1985). A narrative analogy metaphor, one that has explicit implications for the situation to which it refers and is of moderate complexity, was chosen because it has been found to be rated more favorably when used by counselors than either cliches or complex metaphors (Suit & Paradise, 1985).…”
Section: Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Robbins and Haase (1985) study further suggested that the nature of the cues themselves, not the number of cues available, has the greatest impact on ratings of expertness (and attractiveness). A 5th study found that high school students who viewed a counseling session on videotape rated the counselor as expert even after negative reputational cues regarding the counselor had been presented (Littrell et al, 1987).With respect to counselor verbal behaviors, 1 study found that narrative analogies and empathic responses were related to perceived expertness (Suit & Paradise, 1985). Another study found that positive (rather than negative) self-involving statements resulted in higher ratings of counselor expertness (Andersen & Anderson, 1985).…”
mentioning
confidence: 99%